Determinants of Apparel Exports in Developed Economies: Application of the Gravity Model and Economic Geography Theory. (July 2014) - Lee, Juyoung; Karpova, Elena; Lee, Minjung
The purpose of this study was to examine factors that can explain apparel export in economically developed countries. Theoretical framework is based on the gravity model and economic geography theory. Three factors were investigated in relation to apparel export in developed countries: (a) supply of apparel export, (b) potential apparel demand and (c) existence of fashion capital. Secondary data were collected for thirty-one country-members of Organization for Economic Cooperation and Development. Multiple regression analysis showed that apparel domestic supply and potential apparel demand are strong determinants of apparel export in developed countries. The final model explained the 74% of variance in apparel exports from developed countries. Understanding determinants that drive apparel export could facilitate development of new strategies for fostering competitiveness of domestic apparel industries. The results might be beneficial to multinational companies assessing possible apparel production sites for high-value added products.